2021
DOI: 10.18502/jovr.v16i4.9754
|View full text |Cite
|
Sign up to set email alerts
|

Atopobiosis and Dysbiosis in Ocular Diseases: Is Fecal Microbiota Transplant and Probiotics a Promising Solution?

Abstract: Purpose: To highlight the role of atopobiosis and dysbiosis in the pathomechanism of autoimmune uveitis, therefore supporting fecal microbiota transplant (FMT) and probiotics as potential targeted-treatment for uveitis. Methods: This review synthesized literatures upon the relation between gut microbiota, autoimmune uveitis, FMT, and probiotics, published from January 2001 to March 2021 and indexed in PubMed, Google Scholar, CrossRef. Results: The basis of the gut–eye axis revolves around occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The increased of Fusobacterium may cause the disorder of ocular intestinal axis regulation, and lead to the occurrence and disease progression of autoimmune uveitis. Other studies showed that the infection of anaerobic bacteria may aggravate the symptoms of ocular diseases, and the detection of anaerobic bacteria may have the potential to develop into a new generation of diagnostic markers ( Brook, 2001 ; Brook, 2008 ; Gunardi et al., 2021 ). However, compared with healthy subjects, the abundance of Lactobacillus and Lactococcus in OP patients decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The increased of Fusobacterium may cause the disorder of ocular intestinal axis regulation, and lead to the occurrence and disease progression of autoimmune uveitis. Other studies showed that the infection of anaerobic bacteria may aggravate the symptoms of ocular diseases, and the detection of anaerobic bacteria may have the potential to develop into a new generation of diagnostic markers ( Brook, 2001 ; Brook, 2008 ; Gunardi et al., 2021 ). However, compared with healthy subjects, the abundance of Lactobacillus and Lactococcus in OP patients decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…To date there are no studies investigating the role of FMT in treatment of DR; however, this may be a future avenue of study. 130 Finally, flora is an intermediary for many of the molecules implicated in the pathophysiology of DR and may be an avenue for a new generation of therapeutics. Individualized therapy based on the composition of a patient's microbiome may bridge the gap for patients with medically refractive DR.…”
Section: Future Insightsmentioning
confidence: 99%
“…To date there are no studies investigating the role of FMT in treatment of DR; however, this may be a future avenue of study. 130…”
Section: Future Insightsmentioning
confidence: 99%
“…41 In addition, the reconstitution of age-associated gut dysbiosis with FMT from young donors improves aging-driven lacrimal gland circadian dysfunction, reduces lipid deposition and chronic inflammation, and modulates neural activity in aging lacrimal glands by regulating the global rhythmic gene (KEGG) expression in aging exorbital lacrimal glands. 43 Probiotics are living microorganisms that confer beneficial effects on the host organism by competing with potential pathogens or gut commensals and can be used as biotherapy to induce tolerance or modification of the immune system, 44,45 in particular, which are crucial to maintain ocular immune homeostasis and regulate autoimmune dry eye. 46 Recent animal studies of dry eye and probiotics have generally observed that antibiotic treatment increases the risk of dry eye, whereas probiotics can provide clinical benefits to dry eye by reducing inflammatory cell production.…”
Section: Balanced Gut Microbiota Can Relieve Dry Eye Damage and Symptomsmentioning
confidence: 99%
“…Probiotics are living microorganisms that confer beneficial effects on the host organism by competing with potential pathogens or gut commensals and can be used as biotherapy to induce tolerance or modification of the immune system, 44,45 in particular, which are crucial to maintain ocular immune homeostasis and regulate autoimmune dry eye. 46 Recent animal studies of dry eye and probiotics have generally observed that antibiotic treatment increases the risk of dry eye, whereas probiotics can provide clinical benefits to dry eye by reducing inflammatory cell production.…”
Section: Correlation Between the Gut Microbiota And Sjögren Syndrome–...mentioning
confidence: 99%